Photocatalytic degradation evaluation of N-Fe codoped aligned TiO2 nanorods based on the effect of annealing temperature - Abbas Sadeghzadeh-Attar (Journal of Advanced Ceramics, 2020)
Abstract In this paper, a comparative study on the photocatalytic degradation of the Rhodamine B (RhB) dye as a model compound using N-Fe codoped TiO2 nanorods under UV and visible-light (λ ≥420 nm) irradiations has been performed. TiO2 photocatalysts were fabricated as aligned nanorod arrays by liquid-phase deposition process, annealed at different temperatures from 400 to 800 °C. The effects of annealing temperature on the phase structure, crystallinity, BET surface area, and resulting photocatalytic activity of N-Fe codoped TiO2 nanorods were also investigated. The degradation studies confirmed that the nanorods annealed at 600 °C composed of both anatase (79%) and rutile phases (21%) and offered the highest activity and stability among the series of nanorods, as it degraded 94.8% and 87.2% RhB in 120 min irradiation under UV and visible-light, respectively. Above 600 °C, the photocatalytic performance of nanorods decreased owning to a phase change, decreased surface area and bandgap, and growth of TiO2 crystallites induced by the annealing temperature. It is hoped that this work could provide precious information on the design of ID catalyst materials with more superior photodegradation properties especially under visible-light for the further industrial applications.